Nghiên cứu tổng hợp polyme dẫn điện từ ferocen và benzalđehit - Thuận, Ngô Thị; Bắc, Nguyễn Việt; Tuấn, Hoàng Anh (Vietnam Journal of Chemistry, 2014)
The semiconducting polymer based on ferrocene has been synthesized by the poly-condensational reaction of ferrocene with benzaldehyde. The conditions of the reaction include the molar ratio of ferrocene:benzaldehyde as 1:1.3 and the catalytic p-toluene sulfonic acid make linear- soluble polymer. The external conditional reaction as duration of reaction: 60 minutes, temperature: 106±2oC make polymer has Mw: 900 - 1000 dvC and electric conductivity of polymer is s: 10-7S/m